Making new meanings: the entextualisation of digital communications evidence in English sexual offences trials - Daly, Ellen (Crime, media, culture, 2022)
There have been growing concerns about the malleability of digital communications evidence and its potential to reinforce embedded rape myths and cultural narratives that undermine victim-survivors in sexual offences trials. There is however a paucity of research exploring this issue in practice, and none in England and Wales. This article therefore uses two case studies, drawn from court observation research in 2019, to explore how digital communications evidence is used in English sexual offences trials. In both case studies the prosecution argued that digital communications between defendant and victim-survivor constituted admissions of guilt; both defendants resisted this by providing alternative meanings to the well-known colloquial phrases within the messages. Through the process of entextualisation, defence counsel bolstered the meanings defendants attributed to digital communications by drawing upon rape myths and deeply embedded gendered narratives. Defence counsel further employed rape myths and gendered narratives to undermine prosecution entextualisations of the digital evidence. This analysis builds on the existing literature by demonstrating that the malleability of digital evidence extends even to seemingly unambiguous communications.